Di- and Tri-nuclear VIII and CrIII Complexes of Dipyridyltriazoles: Ligand Rearrangements, Mixed Valency and Ferromagnetic Coupling - Rinck, Julia; Kitchen, Jonathan A.; Carter, Anthony B.; Lan, Yanhua; Anson, Christopher E.; Fink, Karin; Brooker, Sally; Powell, Annie K. (Frontiers in Chemistry, 2020)
The first dinuclear and trinuclear chromium(III) and dinuclear vanadium(III) complexes of N4-R-substituted-3,5-di(2-pyridyl)-1,2,4-triazole (Rdpt) ligands have been prepared by solvothermal complexations under inert atmospheres, and characterized. The reactions of CrIII and VIII with adpt (R = amino) resulted in deamination of the ligand and yielded the dinuclear doubly-triazolate bridged complexes [VIII2(dpt-)2Cl4] (1) and [CrIII2(dpt-)2Cl4] (2). In the case of the CrIII complex 2 this bridging results in a rare example of ferromagnetic coupling for a dinuclear CrIII compound. DFT studies confirm that in 2 the ferromagnetic coupling pathways dominate over the antiferromagnetic pathways, whereas in 1 the reverse occurs, consistent with the observed overall antiferromagnetic coupling in that case. It was also found that the use of different additives in the reaction allows the nuclearity of the CrIII product to be manipulated, giving either the dinuclear system, or the first example of a trinuclear circular helicate for a Rdpt complex, [CrIII3(dpt)3Cl6]·1¾MeCN·¼DCM (3). Reaction of N4-pydpt (R = 4-pyridyl) with VIII led to an unusual shift of the pyridyl substituent from N4 to N1 of the triazole, forming the ligand isomer N1-pydpt, and giving a dinuclear doubly-triazole bridged complex, [VIII2(N1-pydpt)2Cl6]·2MeCN (4). Reaction with CrIII results in loss of the 4-pyridyl ring and a mixture of the di- and trinuclear complexes, 2 and 3. Interestingly, partial oxidation of the VIII in dinuclear complex 4 to vanadyl VIV=O was identified by crystallographic analysis of partially oxidized single crystals, [(VIVO)0.84(VIII)1.16(N1- pydpt)2Cl5.16]·0.84H2O·1.16MeCN (5).